Synthesis of formyl-thienylpyrroles : versatile building blocks for NLO materials - Raposo, M. Manuela M. (2006)
Several formyl-substituted 1-alkyl(aryl)-2-(2´-thienyl)pyrroles 3-7 were synthesized by functionalization of the pyrrole or thiophene ring of thienylpyrroles 2 using different methods: Vilsmeier formylation or metalation followed by reaction with DMF.